Quality in Australian outbound student mobility programs : establishing good practice guidelines for international work-integrated-learning in health sciences : final report. - Tan, B-K; Flavell, Helen; Jordan, Joanne; Ferns, Sonia (Australia. Office for Learning and Teaching, 2016)
International fieldwork is accepted as a subset of work-integrated-learning (WIL), which supports students to achieve work-readiness and develop graduate attributes that employers, students and universities desire. These include the development of cultural capability (4-6), key discipline skills in real-world contexts (7-9) and employability skills (10, 11). International fieldwork experiences are considered essential for students to be competitive in the global workforce (12). The value placed on international fieldwork is reflected by the growing trend towards outbound mobility experiences across Australian universities (1, 13). It has also been recognised by the Australian Government with the $100 million New Colombo Plan initiative supporting Australian undergraduate students to study and undertake internships in the Indo Pacific region (14). These trends suggest that there is a need to understand the academic standards required to ensure quality international fieldwork learning experiences, particularly in light of the high costs associated with outbound mobility. At the time of this report, no systematic research had been published on quality processes for Australian international fieldwork in health. Such research is essential to ensure high quality learning experiences for students and appropriate engagement with the communities in which they take place. The aim is to establish academic standards for international fieldwork within health science disciplines, focusing on preparation requirements, the level and model of supervision to monitor fieldwork and assessment criteria to ensure excellent student learning outcomes. [Executive summary, ed]